Determinants and impact of cloud computing implementation in the public sector - Hasimi Sallehudin; Razli Che Razak; Mohammad Ismail (Journal of Advances in Information Technology, 2016)
This study empirically analyses which determinants influence the public sector to implement cloud computing, as well as the effect to performance. Drawing upon the theory on the technology-organization-environment and IS success model, the study hypothesizes that technological, organizational, environmental and human factors can be viewed as the reasons for cloud computing assimilation within the agencies in the Malaysian public sector. Our proposed research model and hypotheses are tested using SEM-PLS and survey data from a sample of 169 agencies in the Malaysian public sector. Our empirical analyses lead to several key findings. All second order factors of Technological, Organizational, Environmental and Human factors affect cloud computing implementation in the Malaysian public sector. Implementation of computing by the agencies significantly affect to IT operational effectiveness. Together, these article offer empirical insights into how cloud computing implementation is influenced by the contextual factors in the Malaysian public sector.